2017
DOI: 10.1074/mcp.m116.062448
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus-Mediated Modification of the Translational Landscape via Virus and Host-Induced Cleavage of Translation Initiation Factors

Abstract: Noroviruses produce viral RNAs lacking a 5′ cap structure and instead use a virus-encoded viral protein genome-linked (VPg) protein covalently linked to viral RNA to interact with translation initiation factors and drive viral protein synthesis. Norovirus infection results in the induction of the innate response leading to interferon stimulated gene (ISG) transcription. However, the translation of the induced ISG mRNAs is suppressed. A SILAC-based mass spectrometry approach was employed to analyze changes to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 76 publications
6
59
0
Order By: Relevance
“…We noted that even in the 335 presence of 2CMC, which inhibits viral RNA synthesis, there was a small but 336 measurable increase in free 80S ribosomes over time in WT cells but not in cells 337 lacking G3BP1 ( Fig 10A). We have previously found that MNV infection results in 338 translation shut off and that this effect is at least partuialkly due to the activity of the 339 NS6 protease (Emmott et al, 2017). The fact we observed 80S accumulation in WT 340 cells, even in the absence of viral RNA synthesis, but not in cells lacking G3BP1, 341…”
Section: G3bp1 Is Required For Viral Negative Sense Rna Synthesis 271mentioning
confidence: 52%
See 1 more Smart Citation
“…We noted that even in the 335 presence of 2CMC, which inhibits viral RNA synthesis, there was a small but 336 measurable increase in free 80S ribosomes over time in WT cells but not in cells 337 lacking G3BP1 ( Fig 10A). We have previously found that MNV infection results in 338 translation shut off and that this effect is at least partuialkly due to the activity of the 339 NS6 protease (Emmott et al, 2017). The fact we observed 80S accumulation in WT 340 cells, even in the absence of viral RNA synthesis, but not in cells lacking G3BP1, 341…”
Section: G3bp1 Is Required For Viral Negative Sense Rna Synthesis 271mentioning
confidence: 52%
“…We have previously found that norovirus infection leads to a translation bias whereby 462 cellular mRNAs induced in response to infection are inefficiently translated (Emmott 463 et al, 2017). Our data suggested that this modification of host cell translation was at 464 least partially driven by the ability of the viral NS6 protease to cleave PABP and the 465 induction of apoptosis which results in cleavage of cellular translation initiation 466 factors (Emmott et al, 2017). Furthermore, we have more recently shown that the 467 ability of the protease to cleave PABP and other substrates is controlled by 468 polyprotein processing and interactions with other viral proteins (Emmott et al, 469 2019).…”
mentioning
confidence: 83%
“…For MNV, production of virulence factor (VF1) antagonized the innate immune response by delaying the production of IFN β [40]. A recent report demonstrated that MNV infection modifies the host response by limiting the translation of host IFN stimulating gene mRNA by exploiting the difference between norovirus VPg-dependent and cellular cap-dependent translation [41]. The actual mechanism that suppresses the host innate immune response to TV infection remains unclear and additional studies are needed to identify the role of VPg during TV infection as well as the role of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used by our labs and many other labs to study translation in neurons (Biever et al , 2015; Perry et al , 2016; Williams et al , 2016), migrating cells (Willett et al , 2011), immune cells (Seedhom et al , 2016) and stressed or infected cells (Kedersha et al , 2016; Emmott et al , 2017; Roth et al , 2017). …”
Section: Introductionmentioning
confidence: 99%